Design and development of urban space products by large-scale robotic extrusion-based additive manufacturing technology - Santos, Afonso Henrique Freitas Ferreira (2024)
AHFE International, vol. 146 "Human aspects of advanced manufacturing, production management and process control: proceedings of the 15th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Nice, France, 24-27 July 2024"